Electrochemical dissolution of titanium under alternating current polarization to obtain its dioxide - Bayeshova Azhar; Bayeshov Abduali; Zhumabay Fatima; Osińska Małgorzata; Łęska Bogusława (Open Chemistry)
The titanium electrode was polarized under the influence of alternating current (AC) at 50 Hz. The current density was varied between 100 and 5,000 A m−2. Initially, the titanium electrode oxidized, and then, titanium oxides were reduced during the cathodic half-cycle of the AC. When the cathodic half-cycle changes to the anodic half-cycle, titanium is oxidized to the trivalent state: Ti−3ē→ Ti3+{{\rm{Ti}}-3{\rm{e}}{\rm{̄}}→ {\rm{Ti}}}^{3+}. The direction of the AC changes depending on its frequency, causing the processes occurring on the electrodes to be periodically repeated. The current efficiency of the titanium electrode dissolution depends on the sulfuric acid concentration and electrolyte concentration, reaching up to 63.4% under optimal conditions. Bipolar electrodes were used during AC electrolysis. It was found that the decrease in the mass of titanium electrodes increases almost linearly at first, from 400 to 1,600 A m−2, and then more intensively within the current densities from 1,800 to 2,500 A m−2. It was shown that when using a bipolar electrode, the total mass loss of the electrodes is 1.38 times greater than the total mass loss during polarization without a bipolar electrode. The composition of the titanium dioxide obtained as a result of electrolysis was identified using physico-chemical analysis methods.